2022
DOI: 10.1039/d2lc00185c
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive lift method for patterning arbitrary-shaped thin ion-selective films in micro/nanofluidic device

Abstract: Micro/nanofluidic platforms with nanoporous films have been utilized as research tools for studying electrokinetic phenomena occurred not only in macro-scale systems such as electro-desalination but also in micro-scale systems such...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…As examples of the introduction of functionalized auxiliary micro/nanostructures to avoid dendrite formation, anodic aluminum oxides (AAOs) and metal–organic frameworks (MOFs) have been introduced on the surface of Li metal as functional separators. , Furthermore, in our recent study, we experimentally and numerically revealed that a negatively charged porous structure with submicrometer pore size as Zn metal hosting layers enhanced the electrokinetic Zn 2+ ion transport in Zn aqueous battery and effectively prevented the metal dendrite formation . Not only to batteries but also to shock electrodialysis and microfluidic biochips for sample separation and preconcentration utilizing ICP, these functionalized auxiliary microstructures such as dielectric porous structures, pillars, or microfin networks , have been systematically applied to control ion transport around ion-selective interfaces. These structures switch the mechanism of ion transport from the EOI governed regime to a more stabilized form of the SC governed regime and/or EOF governed regime to resolve the troublesome problem of flow instability, leading to stable performance.…”
Section: Introductionmentioning
confidence: 93%
“…As examples of the introduction of functionalized auxiliary micro/nanostructures to avoid dendrite formation, anodic aluminum oxides (AAOs) and metal–organic frameworks (MOFs) have been introduced on the surface of Li metal as functional separators. , Furthermore, in our recent study, we experimentally and numerically revealed that a negatively charged porous structure with submicrometer pore size as Zn metal hosting layers enhanced the electrokinetic Zn 2+ ion transport in Zn aqueous battery and effectively prevented the metal dendrite formation . Not only to batteries but also to shock electrodialysis and microfluidic biochips for sample separation and preconcentration utilizing ICP, these functionalized auxiliary microstructures such as dielectric porous structures, pillars, or microfin networks , have been systematically applied to control ion transport around ion-selective interfaces. These structures switch the mechanism of ion transport from the EOI governed regime to a more stabilized form of the SC governed regime and/or EOF governed regime to resolve the troublesome problem of flow instability, leading to stable performance.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, an electrokinetic process called ion concentration polarization (ICP) as a target amplification mechanism is adopted rather than the techniques mentioned above. Within the nanostructure, only the counter ion can pass through it because of the overlapped electric double layer. , This causes an ionic imbalance around the nanostructure, which leads to various physicochemical phenomena such as the formation of an ion depletion zone, a locally amplified electric field in the ion depletion zone, , nonequilibrium space charge, electroconvective instability, and overlimiting currents, etc. Among those unique phenomena, the highly efficient preconcentration of charged species in the electrolyte loaded in the micro/nanofluidic platform (Figure a) can be achieved by this ICP phenomenon .…”
Section: Introductionmentioning
confidence: 99%